Additions of angiosperms to the Flora of Peru from the Andean-Amazonian forests of southern Peru - Huamantupa, Isau (2014)
We present 25 new records of angiosperms for the Peruvian flora, as a result of different botanical explorations conducted in southern Peru, mainly in the areas of the departments of Cusco, Apurimac and Madre de Dios.